The Principle of Effective Demand Effective Demand is a Point! (Papeles, 2019)
This article builds a historical and theoretical journey in its proposal to question the derivation and therefore, the teaching of the IS-LM aggregate demand and supply model as well. An exhaustive presentation is made of each stage of definition, construction and formulation to form the IS-LM model (from Keynesian legacy in The General Theory of Employment, Interest and Money) to show how its construction suffers from a serious logical inconsistency. A reformulation is proposed in the construction and teaching of the model: “not only should the  conventional model of aggregate supply and demand of textbooks be abandoned, but also the 45-degree Keynesian income-expense or cross scheme and of course the model IS-LM.”
Keywords: IS-LM aggregate demand and supply model; Keynes